Research on the Influence Mechanism of Personal Initiative on Enterprise Emergency Management Ability - Li, Shuang; Xu, Feng; Xu, Zhengquan; Kang, Yuqing; Yang, Qifeng (Frontiers in Psychology, 2021)
This study aims to explore the influence mechanism of personal initiative on the overall emergency management ability of enterprises, so as to put forward effective measures to improve the emergency management ability. Based on social interaction theory and feature activation theory, the concepts of organizational support theory, executive power and political skills were introduced to construct a corresponding theoretical model. We collected data through online questionnaire to test this model via structural equation model analysis and regression analysis, with 208 participants of varying background. The results show that personal initiative can strengthen enterprise emergency management ability. The mediating effect of executive power between personal initiative and emergency management ability of enterprise has also been proved. In addition, the two adjustment variables of political skills and perceived organizational support both have a positive impact on the improvement of personal initiative and execution. Therefore, in order to improve the enterprise emergency management ability, it is suggested that enterprises should give full play to the personal initiative, improve the individual and overall executive power. The conclusion of this paper can provide new methodological support for improving emergency management ability.